A method for forwarding materials. - Abdan, Khalina; Wan Hussin, Wan Mohamad Haniffah; Harun, Jalaluddin (2010)

(untitled)
The present invention relates to a machine for forwarding low density material into an extruder or the like comprising a receiving unit (100), first transporting unit (200) and second transporting unit (300) characterised in that an anti-bridging means (201) located between the receiving unit (100) and the first transporting unit (200). The bridging formation defines as the low density material form an arch shape towards the bottom of the receiving unit (100) which prevents the material above the arch shape from fall through the first transporting unit (200). This caused an uneven flow of low density material and consequently interrupts the continuation of feeding process. Hence, the present invention provides a machine for forwarding low density material into an extruder or the like for loosen and breaking the bridging formation.